The House Under the Sea: A Romance - Pemberton, Max, 1863-1950 (Salt Lake City, UT : Project Gutenberg, 2009)
"The House Under the Sea: A Romance" by Max Pemberton is a novel written in the early 20th century. The story follows Jasper Begg, a seaman who embarks on a mysterious journey to Ken's Island, ostensibly at the behest of his former mistress, Ruth Bellenden, who is now married to a foreigner. As he travels, the narrative hints at themes of romantic longing, adventure, and the complexities of human relationships. At the start of the novel, Jasper Begg narrates the context of his voyage aboard the steamship Southern Cross to the Pacific Ocean, where he aims to reach Ken's Island. The crew, initially unaware of their true destination, speculates about the purpose of their journey. As they arrive at the island, Jasper is reminded of Ruth and reflects on their past connection. The opening introduces a sense of mystique and foreboding, as Jasper encounters curious sights and hints at underlying tensions, including the potential danger awaiting him as he seeks to reconnect with Ruth in her new, unsettling surroundings. The atmosphere becomes charged with suspense as he prepares to confront not only the physical challenges of the island but also the emotional complexities of his reunion with Ruth, suggesting a narrative rich in adventure and romantic intrigue. (This is an automatically generated summary.)
Release date is 2009-07-20
E-text prepared by an anonymous Project Gutenberg volunteer
Keywords: Ship captains -- Fiction; Adventure stories; Islands of the Pacific -- Fiction